ANALISIS KEMAMPUAN PENALARAN MATEMATIK SISWA MTs PADA MATERI RELASI DAN FUNGSI - Ulfa Septiani; Fatimah Fatimah; Suswigi Suswigi; Risma Amelia; Wahyu Hidayat (Journal on Education, 2019)
This study aims to analyze the mathematical reasoning abilities of MTs students in Cimahi City on material relations and functions. This study uses a descriptive method with a qualitative approach. The subjects in this study were 25 grade VIII students in one of the MTs in Cimahi City. Data retrieval is obtained by giving a test of mathematical reasoning abilities as many as 5 essay-shaped items. Based on the results of the data analysis, the total percentage of item number 1 of 9% was classified as very low, the question number 2 of 31% was very low, the question number 3 of 14% was very low, the question number 4 was 1% and very number 5 of 59% is classified as moderate, it can be concluded that the mathematical reasoning abilities of class VIII students in one of the MTs in Cimahi in the material relations and functions are still very low. Then the students' mistakes in completing the problem are 1) lack of understanding of the concepts students have, 2) wrong or not careful in carrying out the calculation process and 3) less careful in reading the questions so the answer is less complete.